Cultural Identity as Communicative Accomplishment: Social Identity Processes among Flores Migrants in Surabaya - Fransisca Fitria Kusainintyas; Jefri Setyawan (FAKULTAS DAKWAH UIN SALATIGA, 2026)
This study aims to examine how Flores migrants in Surabaya negotiate and maintain their cultural identity through interpersonal, communal, and digital communication within an urban Javanese setting. The research focuses on the communicative practices of Flores migrant communities and the digital discourse surrounding NTT (Nusa Tenggara Timur) and Flores identity on social media platforms. Employing a qualitative case study design, data were collected through Focus Group Discussions (FGDs) with five Flores migrants in Surabaya and netnographic analysis of YouTube videos and public comments related to NTT identity representation. Drawing on Social Identity Theory, the findings reveal three core themes: (1) boundary communication through embodied markers such as skin color, accent, and ethnic names; (2) constructing belonging through relational language, communal rituals, and traditional dress; and (3) performing pride through digital narratives that counter stigma and affirm cultural heritage. The results demonstrate that digital discourse provides spaces for public articulation of NTT identity, while face-to-face community interactions reinforce solidarity and mutual support among migrants. This study concludes that cultural identity is not merely a psychological resource but a dynamic communicative process through which Flores migrants negotiate difference, recognition, and belonging in multicultural urban life.